PHASE TRANSITIONS IN PYROLITIC MANTLE AROUND 670-KM DEPTH: IMPLICATIONS FOR UPWELLING OF PLUMES FROM THE LOWER MANTLE - Hirose K. (My University, 2002)
Phase relations in the natural pyrolitic mantle composition (KLB-1) around 670-km depth have been determined at 1600–2200°C by high-pressure experiments using multianvil apparatus. A phase transition between majorite garnet and Al-bearing Mg-rich perovskite occurs at depths similar to the postspinel phase transition. The seismic discontinuity observed at this depth could be caused by a combination of both transitions. The majorite-perovskite transition boundary has a positive Clausius-Clapeyron slope (+0.0013 GPa/°C for majorite-out curve), in contrast to the negative slope of the postspinel phase boundary (−0.0028 GPa/°C). Both transition boundaries cross each other at 1700–1800°C. Below this temperature, formation of Mg-perovskite starts at the majorite-perovskite or akimotoite-perovskite transition coexisting with ringwoodite but is predominantly formed by the postspinel phase transition at higher pressures. On the other hand, the stability of majorite significantly expands relative to Mg-perovskite at higher temperatures. Majorite becomes a dominant postspinel phase, and a majority of Mg-perovskite is formed by the majorite-perovskite transition with a positive Clapeyron slope. Phase transition within high-temperature plumes (>1800°C at 670-km depth) assists their upwelling from the lower mantle through the 670-km boundary. The depth of the 670-km seismic discontinuity becomes much less temperature-sensitive and is greater in such a higher temperature region.
Keywords: Pyrolite; 670-km depth; plume; phase transition; lower mantle